Improving the thermal properties of olive/bamboo fiber‐based epoxy hybrid composites. Issue 5 (21st March 2022) - Rashid, Bushra; Jawaid, Mohammad; Fouad, Hassan; Saba, Naheed; Awad, Sameer; Khalaf, Eman; Sain, Mohini
Abstract: In this work, thermal analysis of olive/bamboo fiber‐based epoxy hybrid composites was carried out. Three types of olive fibers, which are olive tree small branch (OTS), olive tree big branch (OTB), and olive tree leaves (OTL), along with bamboo fibers (B), were used to fabricate the composites. Thermal properties of hybrid composites were examined by the thermogravimetric analyzer (TGA), dynamic mechanical analyzer (DMA), and thermomechanical analyzer (TMA). It was found that the thermal stability improved with the incorporation of hybrid fibers in epoxy composites compared to pure fiber composites. Hybrid composite (OTS‐B) exhibited a lower residue (15.82%) whereas hybrid composites (OTB‐B and OTS‐B) show 54.65% and 54.53% weight loss at the maximum decomposition temperature. DMA results showed that the storage modulus and loss modulus reduced with hybrid fiber composites while the damping factor (tan delta) was increased. The storage modulus values of the pure composite sample (B) exhibited a higher increased (3150 MPa). In contrast, the pure composite sample (B) exhibited the highest loss modulus (337 MPa). From TMA analysis, OTL‐B hybrid composite presented a higher T g and lower coefficient of thermal expansion. We concluded that finding from this work will strengthen attracting interpretation of utilization of two different fibers to fabricate hybrid composites for various lightweight purposes in a wide‐ranging choice of industrial applications such as biomedical tools, automobile, and construction fields. Additionally, a novel method can be used to develop hybrid biocomposites materials, which have potential applications in biomaterials and engineering areas.